Kontribusi Budaya Organisasi, Etos Kerja dan Komunikasi Interpersonal Kepala Sekolah Terhadap Motivasi Kerja Guru di SMA Jembatan Budaya - N.N.A. Erawati; I.P.W Ariawan; D.G.H Divayana (Jurnal Administrasi Pendidikan Indonesia, 2021)
The researcher hopes that this research will be able to find out the contribution of organizational culture, work ethic and principal's interpersonal communication to the work motivation of teachers at Jembatan Budaya High School. The researcher used an "ex-post facto" type of research with a total sample of 46 people. Researchers collect data by questionnaires. The researcher calculated the data using simple regression, multiple regression and partial correlation techniques. The conclusions of the study are: (1) found a significant contribution between organizational culture on teacher work motivation with a simple correlation coefficient of 0.51, partial correlation of 0.38 and an effective contribution of 16.24%, (2) found a significant contribution between work ethic and teacher work motivation. with a simple correlation coefficient of 0.45, a partial correlation of 0.43 and an effective contribution of 16.09%, (3) found a significant contribution between the principal's interpersonal communication on teacher work motivation with a simple correlation coefficient of 0.43, a partial correlation of 0.42 and an effective contribution of 14.44%, and (4) and together it was found that there was a significant influence of organizational culture, work ethic and principal's interpersonal communication on teachers work motivation with a double correlation coefficient of 0.69 and a contribution of 47.16% on teacher work motivation. It was concluded that the four variables could be used as predictors of the level of tendency to increase teacher work motivation at Jembatan Budaya Senior High School.